Identification of Numeracy Skills of Elementary School Students in Working on National Assesment Problems - Ristanto, Setya; Rahaju, Endah Budi; Mariana, Neni (International Journal of Emerging Research and Review, 2024)
Objective: The study aims to determine the numeracy skills of students. In addition, this study aims to  determine  misconceptions  in  solving  numeracy  questions  based  on national assessments. Method: This research uses a descriptive qualitative method—data obtained from test results, documentation, and interviews with subjects.  Results:  The results of this study are that the numeracy skills of Genilangit 2 Elementary School have almost the same score as the 2024 Education Report Card score. Overall, the numeracy skills of Genilangit 2 Elementary school students are in the good category. However, it can still be optimized again for a better numeracy score. Students still experience misconceptions (conceptual, procedural, and technical errors) when solving numeracy problems.  Novelty: The novelty of this research is that this research focuses on analyzing the numeracy skills of students who have taken computer-based national assessments done manually on paper. Later, more detailed information will be obtained about the numeracy skills of students and the misconceptions of numeracy students. This research explores detailed information because the questions given are in the form of descriptions so that students' steps in working on problems are known.